The Influence of Barriers on Entrepreneurial Intention Among Students of Business Administration Telkom University - Prilly Amalia Putri; Nuslih Jamiat (Research and Community Services Institutes of Udayana University, 2022)
This research aims to find out the Influence of Entrepreneurship Interest Barriers on Entrepreneurship Interests of Telkom UniversityBusiness AdministrationStudents. The methods used in this research are quantitative with a type of descriptive analysis research. Respondents in this study were 322 Telkom University Business Administration Students with sampling methods namely probability sampling and Proportionate stratified random sampling. The results showed that respondents' responses had an influence of 27.2% between the Financial Barrier variable to the Entrepreneurship Interest variable. There is an influence of 21.5% between the Knowledge Barrier variable to the Entrepreneurship Interest variable. There is an influence of 26% between Risk Avoidance variables to entrepreneurship interest variables. There was an influence of 12% between the Fear of Failure variable on the Entrepreneurship Interest variable, and there was an influence of 9.1% between the Stress Avoidance variable on the Entrepreneurship Interest variable. The results of data processing and analysis showed that the Entrepreneurship Interest Barrier contributed simultaneously to Entrepreneurship Interest by 50.3% while the remaining 49.7% was influenced by other factors outside the Entrepreneurship Interest Barrier variable.